On elementarity of radical classes of modules over noncommutative dedekind duo-domains - Y.T Bilyak; M.Ya Komarnitskii (Karpatsʹkì Matematičnì Publìkacìï, 2012)
We find some sufficient conditions for a radical class of an idempotent radical in the category of modules over a Dedekind left bounded duo-domain to be axiomatizable. In the case of the integer numbers ring this result implies the Gorbachuk-Komarnitskii Theorem on axiomatizable radical classes of Abelian groups.